Cervical Motor and Nociceptive Dysfunction After an Acute Whiplash Injury and the Association With Long-Term Non-Recovery: Revisiting a One-Year Prospective Cohort With Ankle Injured Controls - Kasch, Helge; Carstensen, Tina; Ravn, Sophie Lykkegaard; Andersen, Tonny Elmose; Frostholm, Lisbeth (Frontiers in Pain Research, 2022)
Aims To explore the development of cervical motor and nociceptive dysfunction in patients with whiplash (WPs) and non-recovery based on injury-related work disability 1-year after injury when compared with ankle-injured controls (ACs). Methods A 1-year observational prospective study examining consecutive WPs and age- and sex-matched ACs at 1 week,3 months, 6 months, and 1 year post-injury using semi-structured interviews; global pain rating (VAS0-10) and the pain rating index (PRI-T) and number-of-words-chosen (NWC) from the McGill Pain Questionnaire; examining nociceptive functioning using the cold pressor test (CPT), pressure algometry, and methodic palpation, and central pain processing using counter-stimulation; and examining motor functioning by active cervical range-of-motion (CROM), and neck strength [maximal voluntary contraction flexion/extension (MVC)]. One-year work disability/non-recovery was determined using a semi-structured interview. Results A total of 141 WPs and 40 ACs were included. Total pain rating index (PRI-T) NWC were higher in ACs after 1 week but higher in WPs after 3 months, 6 months, and 1 year. Ongoing global pain was higher in WPs after 1 week and after 3 and 6 months but not after 1 year. Pressure pain thresholds were reduced, and palpation was higher in the neck and jaw in WPs after 1 week but was not consistently different afterward from ACs. Cervical mobility was reduced in WPs after 1 week, 3 months, and 6 months but not after 1 year, and MVC was significantly reduced in WPs when compared with ACs after 1 week and 1 year but not after 3 and 6 months. One-year non-recovery was only encountered in 11 WPs and not in the AC group. Non-recovered WPs (N-WPs) had consistently significantly higher VAS0−10, PRI-T, NWC, reduced pressure pain thresholds, raised muscle-tenderness, reduced active cervical range-of-motion, reduced active-neck-flexion/extension, and reported higher neck disability scores than recovered WPs. Of special interest, there was increasing tenderness in trigeminal-derived muscles based on palpation scores, and marked reduction of PPDT was most pronounced in N-WPs when compared with recovered WPs and ACs. Conclusion Cervical motor dysfunction and segmental nociceptive sensitization were present from early after injury in WPs and prolonged in N-WPs. Differences in trigeminal and cervical motor and sensory function in N-WPs could be of interest for future treatment studies.